2002
DOI: 10.1097/00004032-200207000-00009
|View full text |Cite
|
Sign up to set email alerts
|

MILLIMETER WAVE ABSORPTION IN THE NONHUMAN PRIMATE EYE AT 35 GHz AND 94 GHz

Abstract: The purpose of this study was to evaluate anterior segment bioeffects of pulsed 35 GHz and 94 GHz microwave exposure in the nonhuman primate eye. Five juvenile rhesus monkeys (Macaca mulatta) underwent baseline anterior segment ocular assessment consisting of slit lamp examination, corneal topography, specular microscopy, and pachymetry. These studies were repeated after exposure of one eye to pulsed 35 GHz or 94 GHz microwaves at varied fluences, with the other eye serving as a control. The mean fluence requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 8 publications
1
41
1
Order By: Relevance
“…Under pulse wave conditions, the thresholds for corneal injury, corneal edema, and corneal epithelial defect were found to be 7.5 J/cm 2 for 35 GHz and 5.0 J/cm 2 for 94 GHz [5], suggesting that different frequencies have different ocular effects. These earlier studies employed a circular horn antenna [4,6] or an open-ended waveguide [5]. Because their exposure methodology and experimental animals differed, the results of these studies cannot be directly compared.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Under pulse wave conditions, the thresholds for corneal injury, corneal edema, and corneal epithelial defect were found to be 7.5 J/cm 2 for 35 GHz and 5.0 J/cm 2 for 94 GHz [5], suggesting that different frequencies have different ocular effects. These earlier studies employed a circular horn antenna [4,6] or an open-ended waveguide [5]. Because their exposure methodology and experimental animals differed, the results of these studies cannot be directly compared.…”
Section: Introductionmentioning
confidence: 97%
“…Several in vivo studies in experimental animals have evaluated the specific effects of MMW [4][5][6]. Frequency-specific thresholds for ocular damage were observed at 35 and 107 GHz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both induced similar corneal damage immediately after exposure, the effects of exposure to 35 GHz continued longer than those of exposure to 107 GHz, a difference that may be due to wavelength specificity or relative biological effectiveness. In contrast, a comparison of the threshold of tissue damage between 35 and 94 GHz found that the higher frequency had a lower tissue damage threshold [4]. Depth of penetration of electromagnetic fields into an irradiated object decreases as the frequency of the incident field elevations [7].…”
Section: Discussionmentioning
confidence: 95%
“…Although many studies have assessed the effects of microwave exposure on the eye, few studies have evaluated the specific effects of MMWs [2][3][4][5][6]. Frequency specific thresholds (MMW pulse wave) for ocular damage between 35 and 94 GHz were observed in rhesus monkey eyes, with the mean influence to develop corneal damage being 7.5 J/cm 2 at 35 GHz and 5 J/cm 2 at 94 GHz [4]. In rabbit eyes, 107 GHz effectively produced immediate stromal damage, which was generally gone by the next day, whereas the effects of 35 GHz were persistent and were almost always present the next day [2].…”
Section: Introductionmentioning
confidence: 99%